The acceptance of commercial insurance or takaful during Covid-19 among young working adults in Malaysia - Ang, Shu Yi; Cha, Pui Mun; Chung, Suet Yee; Hee, Jay Min; Tai, Jia Gee (2022)
The General Insurance Industry has stated that there is a significant decrease in the gross direct premiums of commercial insurance or takaful. The objective of this research is to examine the factors affecting the acceptance of commercial insurance or takaful among the young working adults in Malaysia during Covid-19. Four independent variables that used in this study to indicate the factors that influence the acceptance of young working adults to purchase commercial insurance or takaful include awareness or knowledge, attitude, demographic factors (gender, income level, number of family members and occupation) and the attribute of agents. 300 sets of questionnaires were distributed through online in Google Form. IBM SPSS Statistics was used to analyses ad interpret the collected data. The data was analysed using descriptive analysis, reliability test, normality test, Pearson Correlation Coefficient Analysis and Multiple Linear Regression. The result shows that all the independent variables are significant to dependent variable except for the awareness or knowledge of young working adults. Nonetheless, there are some limitations and recommendations in this study that will be further discussed in later chapters.